Decision for biological treatment in real life is more strongly associated with the Psoriasis Area and Severity Index (PASI) than with the Dermatology Life Quality Index (DLQI). (9th June 2014) - Hägg, D.; Sundström, A.; Eriksson, M.; Schmitt‐Egenolf, M.
Abstract Background Following the establishment of the National Quality Registry for systemic psoriasis treatment (PsoReg), the two psoriasis outcome measurements, Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index (DLQI), are now integrated in clinical practice in Sweden. According to current guidelines, the initiation of a biological treatment should depend on a combination of the physician's (PASI) and the patients' assessment of the disease impact on a health‐related quality of life measure (DLQI). Objective To evaluate if either of the two measures, PASI or DLQI, is more strongly associated with initiation of biological therapy. Methods The study is based on 2216 patients suffering from moderate to severe psoriasis who were biological naïve at enrolment to PsoReg. The relationship between the two measures PASI and DLQI and initiation of biological treatment (as outcome) were estimated by a logistic regression and a Cox proportional hazard's model with combinations of PASI and DLQI as independent variables. Results The adjusted regression models showed that patients with high PASI score and low DLQI score had a higher chance to receive biological treatment compared to patients with low PASI score and high DLQI score. Conclusion The decision to initiate biological treatment is more strongly associated with PASI than with DLQI. However, since the DLQI reflects both socio‐economic costs and patient suffering better than PASI, the relevance of the DLQI may be underestimated in clinical practice.